Pattern of Bone Marrow Infiltration in Non-Hodgkin’s Lymphomas - Jamila; Khalid Hassan (Journal of Rawalpindi Medical College, 2008)
Background: Non-Hodgkin’s lymphomas have a predilection for bone marrow involvement, and bone marrow biopsy is performed in an attempt to evaluate stage IV disease. This study was conducted to evaluate the pattern of bone marrow infiltration and morphology of atypical cells in freshly diagnosed patients of Non- Hodgkin’s Lymphomas (NHL). Methods: This prospective, descriptive study was conducted in the Department of Pathology, Pakistan Institute of Medical Sciences (PIMS) Islamabad from January 2003 to December 2004. A total of 50 cases of non- Hodgkin’s lymphoma diagnosed on tissue biopsy, and found to have bone marrow infiltration were randomly selected. The H & E stained trephine sections were examined for evidence of infiltration and pattern of infiltration, viz. focal random, focal para-trabecular, diffuse interstitial and diffuse infiltration. Results: In 52% patients, the infiltration was diffuse; of these patients, 34% showed a complete replacement of normal marrow cellular elements by lymphoma cells, and 18% manifested diffuse interstitial infiltration. An additional 10% cases manifested diffuse as well as diffuse interstitial infiltration. In 30% of patients diffuse or diffuse interstitial infiltration was accompanied with focal random or focal paratrabecular infiltration. Conclusion: Diffuse bone marrow infiltration is much more common in our set-up probably because of a relatively late presentation by patients of non-Hodgkin’s lymphoma